2022
DOI: 10.1002/ps.7272
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive overexpression of EPSPS by gene duplication is involved in glyphosate resistance in Salsola tragus

Abstract: BACKGROUND: Glyphosate-resistant Salsola tragus accessions have been identified in the USA and Argentina; however, the mechanisms of glyphosate resistance have not been elucidated. The goal of this study was to determine the mechanism/s of glyphosate resistance involved in two S. tragus populations (R1 and R2) from Argentina.RESULTS: Both glyphosate-resistant populations had a six-fold lower sensitivity to glyphosate than the S population (i.e. resistance index). No evidence of differential absorption, translo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In contrast, the overexpression of CjCS and OsCS in transgenic tobacco enhances aluminum resistance 24,33 . In addition, overexpression of EPSPs due to an increased gene copy number was found to increase resistance to glyphosate 34 . Overexpression lines with increased gene expression usually show increased resistance to herbicide 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the overexpression of CjCS and OsCS in transgenic tobacco enhances aluminum resistance 24,33 . In addition, overexpression of EPSPs due to an increased gene copy number was found to increase resistance to glyphosate 34 . Overexpression lines with increased gene expression usually show increased resistance to herbicide 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The Pro substitution by Ser at 106 position decreases the binding of glyphosate to the enzyme, diminishing the interaction of the active site of the EPSPS with the herbicide [ 39 ]. In addition to the Pro to Ser substitution, additional alterations in amino acids have been documented at the Pro106 position, including Ala, Gly, His, Leu, and Thr [ 39 , 40 , 41 ]. As a result, the mutated EPSPS gene at the Pro-106 position becomes less sensitive to glyphosate, allowing the EPSPS to maintain proper functionality in the route of shikimic acid in R plants when the herbicide is present.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate-resistance caused by EPSPS gene duplication was demonstrated in a variety of weeds such as Amaranthus palmeri (Gaines et al, 2010), Amaranthus tuberculatus (Lorentz et al, 2014), Amaranthus spinosus (Nandula et al, 2014), Kochia scoparia (Wiersma et al, 2015), Poa annua L. (Brunharo et al, 2019), Chloris truncata (Ngo et al, 2018), Bromus diandrus (Malone et al, 2016), Lolium perenne ssp. Multiflorum (Salas et al, 2012), Salsola tragus (Yanniccari et al, 2023) and Eleusine indica (Chen et al, 2015). However, Laforest et al (2017) reported ACCase gene amplification conferred resistance to ACCase-inhibiting herbicide on crabgrass, indicating that weeds have evolved mechanisms to increase the target gene copy number as resistance to other types of herbicides.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the CYP81A10v7 gene confers cross-pollinated Lolium rigidum multiple-resistance to herbicides with five modes of action: ALS, photosystem II (PS II), 4hydroxyphenylpyruvate dioxygenase (HPPD), acetyl-CoA carboxylase (ACCase) and tubulin inhibitors (Han et al, 2021). The innate resistance of Centaurea to tribenuron-methyl and the cross-resistance to the SU, TP and IMI herbicides are mainly due to metabolism of herbicides by CYP450 and reduced absorption and transport (Palma-Bautista et al, 2023).…”
mentioning
confidence: 99%